The Analysis of Curriculum Merdeka Development in English Education Study Program - Siti Nurrahmah Syahlanudin; Hesty Widiastuty; Zaitun Qamariah (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2023)
Curriculum Merdeka is a diverse and content-optimizing intracurricular learning curriculum that gives learners enough time to explore concepts and strengthen their competencies. The development of this independent curriculum has implications for many things, namely changes in the previous curriculum, changes in learning models, learning media, evaluation of learning outcomes, and last but not least, the collaboration of universities with other universities that characterize the independent campus. The purpose of this study is to analyze the development of the Independent Curriculum that runs in the English Tadris study program, IAIN Palangka Raya. This research uses qualitative approach method. Researchers collect data use the Data that can then be processed and described properly regarding the development of the Independent Curriculum in the English Tadris study program, IAIN Palangka Raya.